Pengaruh Jenis Alat Pengering Terhadap Karakteristik Fisik, Kimia dan Organoleptik Sup Labu Kuning Instan - Rif’an Rif’an; Nurrahman Nurrahman; Siti Aminah (Universitas Muhammadiyah Semarang, 2017)
ABSTRACTPumpkin has many contained a beta-karoten and antioxidant useful to maintain a body health. The diversification of pumpkin to be an instant soup was purposed to increase a economic value and determine for a dryer machine which was optimal and efficient to be a dryer for instant pumpkin soup. The method of this research was experiments methods using completely randomized design (RAL) monofactorial. The factor of this research was kind of dryer machine with drying treatment (cabinet dryer, vacuum dryer, oven dryer and drum dryer). The tests performed were the physical properties (Kamba density, yield and moisture content), chemical properties (Levels of beta-carotene and antioxidant activity), organoleptik characteristic (Taste, aroma, color and texture). Physical and chemical properties data were analyzed by ANOVA, and a further test using Duncan while the organoleptic test results was analyzed using the Friedman test and Wilcoxon test. The results indicated the type of dryer drying significantly different with the physical and organoleptic characteristics of pumpkin soup instant. whereas chemical characteristics were not significantly different. Best instant drying pumpkin soup was obtained from the type of the dryer drum dryer with the best treatment was (Kamba density (0.58 g / ml), yield (32.05%), savory (3.68), fragrance (3.82), viscous consistency (3.68). Keywords: pumpkin, drying, physical, chemical and organoleptic